A New Sensor for Perchlorate Ion - FERNANDES, JR; Kubota, L. T.; Gushikem, Y.; Neto, G. D. (Marcel Dekker Inc, 1993)
A potentiometric sensor for perchlorate anion was developed by mixing a silica gel, chemically modified with 1,4-diazabicyclo (2.2.2)octane, with an epoxy polymer and carbon. The electode showed Nernstian response to the perchlorate ion in the concentration range of 10(-1) and 10(-4) mol L-1.
Keywords: PERCHLORATE; ION SELECTIVE ELECTRODE; CARBON EPOXY MATRIX AND MODIFIED SILICA ELECTRODE